2012
DOI: 10.4028/www.scientific.net/msf.727-728.861
|View full text |Cite
|
Sign up to set email alerts
|

Size Distribution of TiO<sub>2</sub> Nanoparticles Generated by a Commercial Aerosol Generator for Different Solution Concentrations and Air Flow Rates

Abstract: Advances in scientific research in the field of nanotechnology sparked an increase in technological and industrial applications involving nanoparticles, Moreover, there was increasing concern about the control of nanoscale particles released to the atmosphere, driven by concerns over air quality and human health. In this context, this study aims to determine the size distribution of TiO2nanoparticles generated by the commercial TSI Atomizer Aerosol Generator model 3079 for different solution concentrations and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…It is observed that the minimum filtration efficiency was found to be 0.77 for the 0.09 m/s (for dp=150 nm) and greater filtration efficiency was 0.95 for the 0.03 m/s (for dp =20 nm). According [8], this happened because diffusion is the dominant collection mechanism in the removal of nanosized particle and because it's moving is affected by shelling gas, causing irregular moving and collision of particles in fiber of the filter media.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is observed that the minimum filtration efficiency was found to be 0.77 for the 0.09 m/s (for dp=150 nm) and greater filtration efficiency was 0.95 for the 0.03 m/s (for dp =20 nm). According [8], this happened because diffusion is the dominant collection mechanism in the removal of nanosized particle and because it's moving is affected by shelling gas, causing irregular moving and collision of particles in fiber of the filter media.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms of collection by gravity and inertia are predominant with larger particles (above 5µm) with low velocities [7]. According to [8], studies have demonstrated that the predominant mechanism of collection in the removal of nanosized particles is the diffusion, as shown by [6] and [9]. [10] shows that the global efficiency can be estimated by the sum of all the mechanisms mentioned:…”
Section: Particle Collectionmentioning
confidence: 99%